LITERASI MEDIA BAGI KAUM IBU DI RPTRA DHARMA SUCI - Septyana, Virgitta (Universitas Bunda Mulia, 2018)
ABSTRACT The digital era is carrying information and can be accessed anyone through smartphone in the hands. Hoax is one of the big problem which is often divisive among community. Hence, the importance of media literation for residents so as to have the ability apply thought critical of the mass media and doing so can raise awareness and responsibiloties as citizens.This society’s empowerment activity involving the writer takes place at RPTRA Dharma Suci. The reason choosing women is to become a gate keeper who will filter the news for the children. With the collaboration between presentation and study case, women are expected to distinguish the right information or not. Keywords: Media Literation, News, Gate Keeper